Konsep Environmentalisme dalam Al-Qur'an - Muhammad Saiful Anam (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2020)
Natural damage that occurred in almost all parts of the world in the last decade has become a hot issue and makes it a cause for concern. Environmental problems invite and ask various sides to give their best contributionsto effort in saving nature. Not simply for ecological scientists, but the Quran interpreters also contributed to rescue for nature. Since the 6th century, Islam has been present in giving attention to the environment. By means of the Quran, Islam has also given the task to humans who are caliphs on earth to be fair and not do damage to nature. This problem leads to the understanding of the Quran interpreters including M. Quraish Shihab. In tafsir al-Miṣbāḥ, he included the concept of environmentalism to clarify verses about the environment. His idea in providing solutions related to environmental problems is seen through efforts that can be made in the form of making legal regulations; establish cooperation between goverments, companies, communities and academics; maintaining natural recources; reforestation; and be friendly to the environment